(untitled) (Dhaka University Journal of Science, 2013)
An analysis is carried out to investigate the effects of MHD free convection heat transfer of power-law non-Newtonian fluids along a stretching sheet. This has been done under the simultaneous action of suction, thermal radiation and uniform transverse magnetic field. The stretching sheet is assumed to continuously moving with a power-law velocity and maintaining a uniform surface heat flux. The governing nonlinear partial differential equations are transformed into a system of nonlinear ordinary differential equations using appropriate similarity transformations. The resulting non-linear equations are solved numerically using Nachtsheim-Swigert shooting iterative technique along with sixth order Runge-Kutta integration scheme. Numerical results for the non-dimensional velocity and temperature profiles are shown graphically and discussed. The effects of skin-friction coefficient and the local Nusselt number which are of physical and engineering interest are studied and presented in the form of tables for the variation of different physically important parameters. A comparison of the present study is also performed with the previously published work and found excellent agreement. Dhaka Univ. J. Sci. 61(1): 97-104, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15104